Caste interaction in a village tribe: an anthropological case study of the tribes in Dhanaura village in Mirzapur district of Uttar Pradesh - Sankdher, L.M. (New Delhi, 1974)
The present study is an attempt to in vestigate and analyse tribal caste interac ticrs an org the tribal people of Dhan aura village in Mirzapur district of Uttar Pradesh. This anthropological case study was conducted at the Department of Anthropology, University of Luck now, under the supervision of an out standing anthropologist, the late professor D.N. Majumdar. I am indebted to the late Professor Majumdar without whose guidance this micro-study would have never fructified. Professor D.K. Sen and Mr. L.K. Mahapatra gave me valueable suggestions in collection and systemati sation of the entire material.
Keywords: Tribes India